PKM Memberikan Pemahaman dan Pengelolaan Koperasi kepada Pemuda Karang Taruna Kelurahan Bedahan Depok (Neolectura, 2020)
This training provides understanding to participants so that they can get to know and manage cooperatives for the welfare of members. The participants are expected to be able to recognize the types of cooperatives, cooperative groups, cooperative businesses and know how to manage cooperatives properly and correctly. Furthermore in the training, there was also an understanding of the conditions for establishing a cooperative. The participants were also given an understanding of the importance of documents in the form of permits that must be owned by the cooperative when it has been established and the business is already underway. Participants will be given a stamp on cooperative management, cooperative working capital consisting of principal savings, mandatory savings and voluntary savings, all of which come from members. After that the participants were given material about calculating the remaining results of operations that must be shared with members each year known as the SHU and Annual Member Meetings (RAT) which must be held by the management every year. The participants of this training are small entrepreneurs and small traders and residents who are and operate in the RT.03 RW.09 area located on H. Saenan Street, Bedahan Village, Sawangan District, Depok. From the results of the survey that we conducted, participants generally had a high enough interest to learn about Cooperatives as the core material of the activity. The obstacle they face is how to start a cooperative business so that citizens can experience first hand the benefits of cooperatives.